Anti-PD-1/PD-L1 for nasopharyngeal carcinoma: a comprehensive analysis of registered trials on ClinicalTrials.gov - Dai, Zelei; Li, Nian; Wang, Jun; Tan, Chenfeng; Zhang, Yonggang; Liu, Lei (Frontiers in Pharmacology, 2023)
Objective Clinical trials play an important role in the development of healthcare. However, the current status of clinical trials on anti-PD-1/PD-L1 for nasopharyngeal carcinoma remains unclear.Therefore, this study aims to provide a comprehensive analysis of the registered trials related to anti-PD-1/PD-L1 for nasopharyngeal carcinoma on ClinicalTrials.gov.Methods A search was conducted on the ClinicalTrials.gov database to identify all registered trials related to anti-PD-1/PD-L1 for nasopharyngeal carcinoma up to February 26, 2023. The characteristics of the trials were examined, and the studied drugs, disease conditions, as well as details of trials with available results were analyzed. Publication status was assessed by a PubMed search using the ClinicalTrials.gov NCT number.Results A total of 112 interventional clinical trials registered between 2015 and 2023 were included. Of the trials, 90 were carried out in Asia, 72 were in phase 2, and 31 trials had either companies or universities as sponsors/collaborators. The sample sizes across the trials varied greatly, with a median of 71.5 participants per trial. The majority of trials were recruiting participants, with only 6 had posted results. PD-1 inhibitors were preferred over PD-L1, and Toripalimab emerged as the most extensively studied drug. About one-third (33.9%) of the studies looked into recurrent/metastatic nasopharyngeal cancer.This study provides an overview of all registered trials of anti-PD-1/PD-L1 for NPC. It is needed to improve the completeness, outcome selection, randomization and masking of trials and to be transparent and timely in reporting of results.